Mixed mode (I/II) fracture energy of cement emulsified asphalt mortar under intermediate temperature. (January 2021) - Najjar, Shima; Mohammadzadeh Moghaddam, Abolfazl; Sahaf, Ali
Highlights: Intermediate temperature fracture behaviors of cement emulsified mortar were investigated. Fracture behaviors for tensile, shear and mixed tensile-shear were measured. D-Optimal Mixture Design Method was employed. Regression models based on the experimental results were developed. Dependence of fracture mode I, II and I/II on mix desgin ratios was demonstrated. Highest fracture energy belonged to the pure shear mode and the lowest was related to the pure tensile mode. Optimum designs for maximizing fracture toughness of all three modes was delimited. Abstract: Being a combination of sand, cement, water, and asphalt emulsion, Cement Emulsified Asphalt Mortar (CEAM) has better toughness and flexibility properties than cement mortar. Given the multiphase nature of CEAM, it is susceptible to micro-cracking during the setting process and also due to other factors such as traffic loads, undesirable atmospheric conditions. Given the typical direction of loading and cracking in these mortars, they are likely to experience mixed-mode fractures. Therefore, this study investigated the fracture properties of CEAM at service temperature in mixed mode I&II fractures. For this investigation, the mixed-mode fracture energy was determined through experiments on Semi-Circular Bending (SCB) specimens with the volume fractions of mortar treated as independent variables and the material behavior assumed to be viscoelastic at ambient temperature. Considering the need to investigate the effect of mix design ratios and their interactions, to reduce the number of experiments, and to limit these ratios to the ranges that produce acceptable rheological and mechanical properties, the D-Optimal mixture design method at 5% significance level was used to optimize the design of experiments and related analyses. Next, a regression model was developed for the relationship between fracture energy in each mode (I, II, I&II) and the mortar constituents. Also, the optimum mix design range to reach maximum fracture energy in all three modes was determined by graphical optimization. Analysis of the results with ternary contour plots showed the dependence of fracture energy and the optimum mix design range in the studied modes on the mix ratios of the CEAM constituents. The Cement and asphalt were identified as the independent variables with greatest effects on fracture energy variations and the optimum mix design. The results also revealed that as the asphalt emulsion-to-cement ratio increased, the maximum carried force decreased and the deformation corresponding to this force increased.